1990
DOI: 10.1111/j.1465-7287.1990.tb00645.x
|View full text |Cite
|
Sign up to set email alerts
|

Subsidy to Nuclear Power Through Price‐anderson Liability Limit

Abstract: Between 1959 and 1982, the Price-Anderson Act placed a limit of $560 million on the liability of nuclear power plant operators for accidental damages. This limit grew to $7 billion due to the 1988 amendments to the act. This paper using insurance premiums charged for the first $160 million of coverage and the Nuclear Regulatory Commission's estimate of the probability of a worst-case loss, models the distribution of damages with a log-logistic density function. The study finds that the value of the Price-Ander… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 1 publication
0
23
0
Order By: Relevance
“…Even today, nuclear power remains un-insurable in the free market [61] and governments have had to provide some form of limited liability for nuclear utilities for any company to consider building a reactor. Largely depending on the geographic location of the nuclear power plant, the devastating economic consequences of a catastrophic nuclear accident are in the order of hundreds of billions [65][66][67]. Thus, the U.S. Nuclear Regulatory Commission (NRC) concluded that the liability limits were sufficiently significant to constitute a "subsidy"; however, a quantification of the amount of this nuclear insurance subsidy was not attempted [68].…”
Section: Nuclear Energy Economic Sustainability and Insurabilitymentioning
confidence: 99%
“…Even today, nuclear power remains un-insurable in the free market [61] and governments have had to provide some form of limited liability for nuclear utilities for any company to consider building a reactor. Largely depending on the geographic location of the nuclear power plant, the devastating economic consequences of a catastrophic nuclear accident are in the order of hundreds of billions [65][66][67]. Thus, the U.S. Nuclear Regulatory Commission (NRC) concluded that the liability limits were sufficiently significant to constitute a "subsidy"; however, a quantification of the amount of this nuclear insurance subsidy was not attempted [68].…”
Section: Nuclear Energy Economic Sustainability and Insurabilitymentioning
confidence: 99%
“…The work presented by Dublin and Rothwell is conservative (e.g., no health effects are included in the analysis). Thus, the estimated insurance subsidy per reactor was $60 million in 1982 [24]. The 1988 amendments to the PAA increased the total provided coverage to $7 billion, which consequently reduces the subsidy per reactor to $22 million.…”
Section: The Price-anderson Act (Paa) and Us Government Indirect Numentioning
confidence: 99%
“…To date, the most complete and comprehensive analysis was performed by Dublin and Rothwell in 1990 [23]. The study [24] aimed to compare the insurance premiums nuclear power plant operators currently pay under the PAA to the premiums weathered if facilities were responsible for full liability coverage in the absence of PAA limits. The work presented by Dublin and Rothwell is conservative (e.g., no health effects are included in the analysis).…”
Section: The Price-anderson Act (Paa) and Us Government Indirect Numentioning
confidence: 99%
“…These costs are called loading costs and refer to the overheads generated by the normal functioning of the insurance (administration charges, management costs, etc.). They are traditionally estimated to be about 30% of the objective value of the risk (Dubin and Rothwell 1990;Liston-Heyes 1998, 2000). If we take them C = c Á E(x), with c = 0.3, Eq.…”
Section: The Calculation Of the Insurance Premiummentioning
confidence: 99%